MENINJAU IMPLEMENTASI PROGRAM INOVASI RANTANG KASIH BAGI KESEJAHTERAAN LANSIA MISKIN SEBATANGKARA DI DESA BANJAR, KABUPATEN BANYUWANGI - Ali Wafa (Politeknik Kesejahteraan Sosial Bandung, 2022)
Background: There are quite a lot of elderly people in Banyuwangi Regency who do not have families and cannot work because of their weak physical condition, This condition is called the poor elderly alone as Persons with Social Welfare Problems (PMKS). The health and welfare of the elderly will continue to be concerned if the public and government concerns do not take sides, Rantang Kasih is an innovation program of the Banyuwangi Regency Government as an alternative solution to this problem. Objective: This study aims to describe the condition of the elderly's welfare, and to review the suitability between the Rantang Kasih program guidelines and the field reality, the implementation of the Rantang Kasih program in the Banjar Village environment. Research Methods: Using a qualitative approach, data collection obtained through interviews, literature study and documentation. There are 25 elderly living in Banjar Village as program targets or beneficiaries. Research Results: The results showed, there needs to be an increase and clarity in the amount of food, specifying standard food menus, the type of food packaging used, presenting the role of volunteers and social workers, and also the need for program development by expanding the target beneficiaries, to potential elderly with vulnerable economic and welfare status